High tech meets high touch in upscale hotels - Brochado, A. (2016)
Purpose: This paper presents an analysis of the impact of current technologies on customer experiences in upscale hotels and assesses the potential of the latest technologies for enhancing customers’ stay. Design/methodology/approach: A two-step approach was applied in this study. The qualitative phase included an examination of upscale hotel websites, interviews with hotel managers and an internet search regarding the latest technological innovations in hotels. In the quantitative stage, a questionnaire was developed for hotel guests, generating a sample of 310 valid completed questionnaires. Findings: The results reveal that hotel guests value digital involvement in their hotel experience. Moreover, business travellers and younger generations give greater importance to latest technologies. Originality/value: This study analyses the most innovative technologies, providing guidance for hoteliers wishing to upgrade or implement new technologies. Based on the findings, hoteliers can achieve greater differentiation by offering the most important and latest technology to guests, enhancing their experience and attracting new customers, which can potentially lead to increased revenues. The study’s results are also important because they include the perceptions of both managers and customers.